Multicriteria Analysis Of Impacts Of Distributed Generation Sources On Operational Network Characteristics For Distribution System Planning Concerning Steady-state And Transient Operations - Barin, Alexandre; Pozzatti, Luis F.; Machado, Ricardo Q.; Canha, Luciane N.; Farret, Felix A.; Abaide, Alzenira da R. (Eletrônica de Potência, 2009)
Recent advances in power generation technology and new directions in the Brazilian electricity regulation allowed wide spreading of the distributed generation (DG), with some consequent impacts on operational characteristics of the distribution networks. So, new methods for identifying such impacts become necessary in research and development of new tools and resources to maintain and ease the continued expansion towards DG deployment. Initially, this paper presents a study aiming at determination of the appropriate DG locations within distribution systems. This analysis presents a multicriteria analysis to define some qualitative and quantitative parameters using fuzzy logic to determine the appropriate DG sites. In this direction, the paper analyzes transient effects on the feeder power flow from which it is possible to determine the minimal conditions for guaranteeing DG reliability and high power quality. The considerations and results described in this paper make part of the Research & Development Program developed by the State Company for Electric Energy (CEEE) and the Federal University of Santa Maria (UFSM), Brazil.